1989
DOI: 10.1007/bf00643511
|View full text |Cite
|
Sign up to set email alerts
|

The fatigability of two agonistic muscles in human isometric voluntary submaximal contraction: an EMG study

Abstract: The recruitment and firing rate of biceps brachii (BB) and brachioradialis (BR) motor units (MUs) were studied in the course of fatiguing isometric contractions at 20%-30% of maximal voluntary contraction (MVC). MU recruitment generally occurred throughout the maintained contraction and was similar for BB and BR muscles. Newly recruited MUs started to discharge in the form of bursts, the duration of which increased until a continuous rhythmical firing was achieved. Within each burst, the first interval between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 22 publications
10
86
0
3
Order By: Relevance
“…To compensate for the reduction in motor unit force, the net muscle force is maintained by a gradual increase in the descending drive that recruits previously inactive motor units (Löscher et al 1996). Once activated, the newly recruited motor units discharge action potentials either repetitively or intermittently (Bawa et al 2006;Carpentier et al 2001;Fallentin et al 1993;Garland et al 1994;Maton and Gamet 1989;Miller et al 1996) and the previously active motor units may either continue to discharge action potentials or cease to discharge action potentials for the remainder of the contraction (Person 1974) or until the motor unit has recovered sufficiently to resume activity (Bawa et al 2006). Riley et al (2008) found that the discharge characteristics of motor units at recruitment could differ substantially, depending on the difference between the recruitment threshold of the motor unit and the target force for the sustained contraction.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the reduction in motor unit force, the net muscle force is maintained by a gradual increase in the descending drive that recruits previously inactive motor units (Löscher et al 1996). Once activated, the newly recruited motor units discharge action potentials either repetitively or intermittently (Bawa et al 2006;Carpentier et al 2001;Fallentin et al 1993;Garland et al 1994;Maton and Gamet 1989;Miller et al 1996) and the previously active motor units may either continue to discharge action potentials or cease to discharge action potentials for the remainder of the contraction (Person 1974) or until the motor unit has recovered sufficiently to resume activity (Bawa et al 2006). Riley et al (2008) found that the discharge characteristics of motor units at recruitment could differ substantially, depending on the difference between the recruitment threshold of the motor unit and the target force for the sustained contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an initial, brief IPI has been reported to occur during voluntary activation of human motor units [13][14][15]. Therefore, the constant frequency pattern of stimuli that is used during conventional electrical stimulation may not be similar to what occurs under voluntary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fatigue causes MU recruitment, and the MU firing rate increases as a function of the elapsed time. These changes are not reflected in the EMG changes which occur during fatiguing isometric contraction of the arm flexors at 20-30% MVC (Maton & Gamet, 1989). However, it was recently found that the changes due to fatigue in the sEMG signal (increased amplitude and decreased frequency) suggest that the recruitment of MU firing rates correlates with sEMG amplitude (Calder et al, 2008).…”
Section: Application Of Emg In Muscle Fatigue Researchmentioning
confidence: 97%